URGENSI PEMBELAJARAN SAINS DALAM MENINGKATKAN MOTIVASI BELAJAR PADA ANAK USIA DINI - Kurnia, Selia Dwi (Institut Agama Islam Negeri Bone, 2019)
This article is about the stimulation of early childhood learning motivation through science learning. Play activities in children will be easier motivate through science learning. This provides an opportunity for children to do directly science games, thus providing more motivation in learning process. Science learning in the form of play activities makes simple experiments that can lead to the process, observation, prediction, and communication, and other skills of children.Keywords: Childhood Learning Motivation, Science Learning.